OTENTISITAS SUNNAH DAN KEDUDUKANNYA DALAM LEGISLASI HUKUM ISLAM - Nur Kholis Hauqola (Al-Ahkam, 2014)
This paper aims to discover the truth of the authenticity of the Sunnah as the basis of Islamic law legislation. The problem lies on the "doubt" polemic of the existence of Sunnah considering the length of time from the time of codification. Namely, on how the Sunnah "made" and defended as genuine (authentic) sources derived from the Prophet. How did the position of the Sunnah in Islamic law legislation that he deserves obeyed. To find out the answer to these problems, this study analyzes literatures related with, both the "pro-Sunnah" and the "counter-Sunnah", both from the insider and outsider. The conclusion is that the question of the authenticity of the Sunnah always raises debate over writing, history, until the issue of trustworthiness to it. This problem not only sparked debate in relation Muslims and non-Muslims, even among fellow Muslims themselves.